2022
DOI: 10.3389/fbinf.2022.932114
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the molecular mechanism of iguratimod act on SLE using network pharmacology and molecular docking analysis

Abstract: Objective: Iguratimod (IGU) is a novel small disease-modifying compound widely used in Asia for the treatment of rheumatic diseases. IGU is a methane sulfonanilide. We applied network pharmacology to investigate the pharmacological mechanisms of IGU act on SLE.Methods: We used PharmMapper, UniProt, and OMIM databases to screen the potential targets of IGU, and the SLE-related disease targets were predicted. Hub target genes among the intersections of the potential targets (IGU) and related genes (SLE) were val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The molecule structure was compared with relevant literature, and its CAS number and 2D structure map were used to draw a 3D structure map on ChemDraw, resulting in an exported sdf format file. The sdf file was uploaded to PharmMapper for target prediction, and the Uniprot ID obtained was converted to Geneofficial ID on the UniProt platform 20 .…”
Section: Methodsmentioning
confidence: 99%
“…The molecule structure was compared with relevant literature, and its CAS number and 2D structure map were used to draw a 3D structure map on ChemDraw, resulting in an exported sdf format file. The sdf file was uploaded to PharmMapper for target prediction, and the Uniprot ID obtained was converted to Geneofficial ID on the UniProt platform 20 .…”
Section: Methodsmentioning
confidence: 99%
“…Based on network pharmacology and molecular docking, some studies have revealed the potential therapeutic mechanism of Iguratimod on SLE protein targets through PI3K-AKT signaling pathway, MAPK signaling pathway and FoxO signaling pathway (123). In the study of lupus kidney, Chen et al used Pristane to induce the kidney of systemic lupus erythematosus (SLE) mice.…”
Section: Iguratimod In the Treatment Of Sle And Lupus Nephritismentioning
confidence: 99%
“…Based on the network analysis, two active components (glyceryl linolenate and βsitosterol) and four targets (PTGS2, CASP3, CASP8, and CASP9) were screened by phar-macology analysis for molecular docking. The simulated docking and relevant parameters are shown in Figure 7 and Table 3, in which a binding energy of less than −5 kcal•mol −1 indicated a strong binding force [49]. Based on this criterion, the binding sites on the four target proteins were all abundant for β-sitosterol to form firm bindings.…”
Section: Molecular Dockingmentioning
confidence: 99%